Factors showing impact on high school student’s academic performance using ANOVA - S B V J, Chand Badshah; Kumar, K Siva; Prakash, PC; Krishna, M. Gopala (IJRDO - Journal of Applied Management Science, 2016)
This study investigated the factors that shows impact on high school student’s academic performance.357 (Male =182; Female =158) high school students were randomly chosen as the sample of the study in government high school located in rural area of Tirupati. The demographic questionnaire was used to collect respondents’ bio-data while their half yearly examination results were used as a measure of academic performance. The focus of this research is that student performance in Half yearly examination is linked with students’ outline consisted of his approach towards communication, learning facilities, proper guidance and family stress. Analysis of Variance and t-test Analysis were used to analyse the data.